Caring Behavior of Nurses In Providing Nursing Care Patients During The Covid-19 Pandemic - Daulay, Wardiyah; Sitanggang, Rahmatia (Caring: Indonesian Journal of Nursing Science, 2023)
During the Covid-19 pandemic, a lot of nursing care was missed due to the increasing demands for patient care, the high risk of infection, physical and mental fatigue, things that make health workers experience this, one of which is because the high workload couses fatigue in implementing nurses and the cessation of caring behavior. This study aims to identify the caring behavior of implementing nurses in providing nursing care to patients in the Inpatient Room at the Universitas of North Sumatra Hospital during the Covid 19 Pandemic Period. The design used descriptive with a quantitative approach. Sampling used a non-probability sampling technique with a purposive sampling. Samples that met the inclusion criteria were 40 nurses and 40 patients. Data was collected using a questionnaire caring behaviors inventory (CBI). Of all the statement items, the highest score was on the assurance of human presence subscale, providing timely care and treatment of patients with an average score of 5.33 with a median value of 5.00. Meanwhile, according to the patient's perception of the caring behavior of the implementing nurse, the highest score is on the assurance of human presence subscale, talking to patients with an average value of 5.20 with a median value of 5.00. It can be concluded that the perception of the implementing nurse as the provider of nursing care and the patient as the recipient of nursing care have different perceptions about caring behavior. This research is expected to be input for nursing services to improve caring behavior.